Using latent profile analysis to uncover the combined role of anxiety sensitivity and test anxiety in students’ state anxiety - Journault, Audrey-Ann; Plante, Isabelle; Charbonneau, Sandrine; Sauvageau, Claudia; Longpré, Charlotte; Giguère, Charles-Édouard; Labonté, Carolanne; Roger, Kassandra; Cernik, Rebecca; Chaffee, Kathryn Everhart; Dumont, Laurence; Labelle, Réal; et al. (Frontiers in Psychology, 2022)
Background Studies report a growing tendency for students to experience state anxiety in schools. However, the combination of individual susceptibilities likely to trigger students’ anxious states remains unclear. Aims This study examined whether distinct profiles of students emerge regarding their susceptibility to anxiety sensitivity and/or test anxiety and evaluated whether students’ profile predicted anxious states. We also verified whether susceptibility profiles varied across gender, school level, and school type. Sample and methods In total, 1,404 Canadian students in Grades 5 and 10 (589 boys; Mage = 15.2, SD = 2.1) from 13 public and private schools completed self-reported measures of state/trait anxiety, anxiety sensitivity, and test anxiety. Results Latent profile analyses identified four susceptibility profiles: (1) Double-susceptibility: highest anxiety sensitivity and test anxiety scores; (2) Unique-susceptibility to test anxiety: high test anxiety score and low anxiety sensitivity score; (3) Unique-susceptibility to anxiety sensitivity: high anxiety sensitivity score and low test anxiety score; and (4) No-susceptibility: lowest anxiety sensitivity and test anxiety scores. The profiles comprised 12, 9, 6, and 73% of the sample, respectively, and their membership varied across gender and school type, but not across school levels. A linear mixed-effect model showed that state anxiety varied significantly between profiles, where the Double-susceptibility profile predicted the highest state anxiety scores, followed by the two Unique-susceptibility profiles (indifferently), and the No-susceptibility profile. Conclusion Beyond their theoretical contribution to the state–trait anxiety literature, these findings suggest that selective interventions designed more specifically for students with the Double-susceptibility profile may be worthwhile. Results also highlight the high proportion of students with the No-susceptibility profile and shed light on the reassuring portrait regarding students’ anxiety.